Development of Religious and Moral Values Through Cublak-Cublak Suweng Traditional Games To Build Children's Character - Retno Anggraini; Astri Wahyuni (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
One way to build character early is through games, including traditional games. Apart from building character, this game can also develop aspects of children's religious and moral values. The purpose of this research is to make children's character. The type of research used in this research is descriptive research with an inductive approach, data collection techniques used are primary and secondary data through inductive methods. Based on the results of research that has been carried out, it shows that traditional games performed for early childhood using cublak-cublak suweng games can help train and develop the development of religious and moral values ​​in children aged 4-6 years by training children to behave well, honest, polite behavior, tolerance, train cooperation, and train children's creativity.